Peculiarities of identification and customs commodity examination of children’s goods - H. V. Tyshchenko; R. V. Kravchenko (Bulletin of Kharkiv National University of Internal Affairs)
Special attention is paid to the issue of identification and safety of children's products, which is aimed at ensuring the safety and quality of this category of goods. In the scientific article, the issue of classification of goods of group 95 in accordance with the Ukrainian Commodity Nomenclature of Foreign Economic Activity was considered, and a study of the practice of appointing customs examinations was conducted. The main identifying features of the classification of scooters in the category of goods for children are: purpose; design features, their modification; type of movement; number and diameter of wheels; type of ride Attention should also be paid to the following identification features of children’s goods, which are necessary both during customs control and during the examination of toys: the size of the toy, the material of manufacture, design features, application and main functional purpose. The development and improvement of current methods of identification of toys will simplify the procedure of their inspection and increase the objectivity of the results. The work summarizes the ways to classify children’s scooters in the procedure of commodity examination. The diagnostic tasks of the forensic commodity examination to determine safety, compliance with standards, which the expert must solve during the study of a children’s scooter, are defined. State-of-the-art research methods, in particular, visual inspection, functional tests, measurement of geometric parameters, mechanical tests, chemical analysis of materials, technical expertise, safety tests, computer modeling and analysis, electrical and electronic tests, expert evaluation are used to establish indicators. quality and safety of goods and obtaining objective information. The main identification tasks of the commodity examination of children’s scooters, the most typical defects of these products and defects that indicate their low quality are indicated. The mechanism of forensic commodity examination of children's scooters is described.